HUBUNGAN TINGKAT KECEMASAN DENGAN PENINGKATAN TEKANAN DARAH PADA PASIEN PRE OPERASI BENIGNAPROSTAT HIPERPLASIA (BPH) DI RSUD PROF Dr. MARGONO SOEKARJO - Muliana -; Suci Khasanah; Susanti - (Universitas Harapan Bangsa Purwokerto, 2016)
The anxiety experienced by pre-surgery Benign Prostat Hiperplasi (BPH ) patients may lead to the stress like nervous feeling of the operation which furtheraffect the autonomic nervous system. The increase of adrenal glands releaseadrenaline, which causes the body to increase the heart frequency.Anxiety causesthe cognitive, psychomotoric, and physiological responses, one of them is anincrease in the blood pressure. The purpose of this study was to know the correlation between anxietylevels and blood pressure increase on patients of pre- surgery benign prostatehyperplasia (bph) in prof. margono soekarjo hospital purwokerto 2016. The type of this research was descriptive correlation with cross sectionalapproach. The sampling technique used consecutive sampling, while the samplesof this study were the patients who underwent surgery for BPH in Prof. Dr.Margono Soekarjo Hospital Purwokerto as many as 30 people. Further, thestatistical analysis used Spearman rank analysis. The result of this study showed that half of respondents experiencedmoderate anxiety as many as 15 respondents (50%). Most respondentsexperienced an increase in the blood pressure as much as 19 respondents(63.3%). Hence, it can be concluded that there is a significant correlationbetween the level of anxiety and an increase in blood pressure over pre-surgerypatients with p value: 0.003. Keywords: anxiety, pre-surgery, blood pressure